Analysis of service quality in the character education model of environmental care at SMP IT Dinamika Umat using the importance performance analysis method - Fatimah, Fatimah; Mujahidin, Endin; Saefudin, Didin (Eximia, 2023)
This study aims to analyze the quality of service in the character education model of caring for the environment at SMP IT Dinamika Umat using the Importance Performance Analysis (IPA) method. The study respondents were 30 students who filled out questionnaires to assess the level of importance (Level of Importance / Yi) and level of performance (Level of Performance / Xi) of several attributes that are indicators of service quality. The results showed that there are attributes that have a high level of importance but low performance (Quadrant I), attributes that have a high level of importance and performance (Quadrant II), and attributes with low importance but high performance (Quadrant III). Based on this analysis, this study recommends priority improvement for attributes in Quadrant I, maintenance of achievement in attributes in Quadrant II, and maintaining stability in attributes in Quadrant III to improve the overall quality of service in the model of environmental care character education at SMP IT Dynamics Umat.